Judging a Man by the Width of His Face: The Role of Facial Ratios and Dominance in Mate Choice at Speed-Dating Events. (March 2014) - Valentine, Katherine A.; Li, Norman P.; Penke, Lars; Perrett, David I.
Previous research has shown that men with higher facial width-to-height ratios (fWHRs) have higher testosterone and are more aggressive, more powerful, and more financially successful. We tested whether they are also more attractive to women in the ecologically valid mating context of speed dating. Men's fWHR was positively associated with their perceived dominance, likelihood of being chosen for a second date, and attractiveness to women for short-term, but not long-term, relationships. Perceived dominance (by itself and through physical attractiveness) mediated the relationship between fWHR and attractiveness to women for short-term relationships. Furthermore, men's perceptions of their own dominance showed patterns of association with mating desirability similar to those of fWHR. These results support the idea that fWHR is a physical marker of dominance. This is the first study to show that male dominance and higher fWHRs are attractive to women for short-term relationships in a controlled and interactive situation that could actually lead to mating and dating.